A COMPARATIVE STUDY OF THE IMAGE OF SISYPHUS IN WESTERN AND UZBEK LITERATURE - Mahmadiyor Asadov (Scholar Express Journal, 2022)
When we talk about the famous legendary hero Sisyphus today, no doubt the French writer Albert Camus comes to mind. So, before our eyes, the brightest aspects of the "absurd hero" are reflected in modern philosophy and literature. Who would not admit that this rebel, cursed by the gods and condemned to eternal punishment, has become a symbol of true humanity to this day. If this Greek hero became famous in any sense, it is due to the essay "The Legend of Sisyphus" (Albert Camus. Le mythe de Sisyphe. 1942), created in 1942. Philosophers, literary critics, literary critics, and even students and readers were able to consciously discover Sisyphus. The famous French philosopher and writer Jean Grenier described Sisyphus as a “hero of forgotten memories,” but in the end, his student and best friend Albert Camus brought Sisyphus to the pinnacle of modern Greek mythology, and he was undoubtedly a hero worthy of it
Keywords: Sisyphus; Greek hero